AKULTURASI BUDAYA SUKU KLUET DAN SUKU ANEUK JAMEE DALAM ADAT PERNIKAHAN DI DESA JAMBO PAPAN KECAMATAN KLUET TENGAH ACEH SELATAN - Zulpandi Zulpandi; Said Fadhlain; Reni Juliani (JIMSI: Jurnal Ilmiah Mahasiswa Ilmu Komunikasi, 2022)
The Ethnic in Jambo Papan Village, Kluet Tengah District, South Aceh is a combination of Aneuk Jamee culture and Kluet culture. No wonder there is a mixing of the two cultures in society, one of which is in the wedding procession that occurs in a mixed marriage of the two Ethnics. This is the background of the problem in this research. The purpose of this study was to find out the meaning contained in the wedding customs in Jambo Papan Village, Central Kluet, South Aceh. The research method used is descriptive qualitative research, with data collection techniques of observation, interviews and documentation. The results showed that there were only four traditions that interfered with Kluet culture in Jambo Papan Village, namely: the meubobo tradition, ridi was berngi or bathing baluluk, night bainai or berngi meukacar and the tradition of murih rice. This is because the residents of Jambo Papan Village have the concept of